2013
DOI: 10.1016/j.jadohealth.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning: Associations With Weight Status, Eating Behaviors, and Physical Activity in Adolescents

Abstract: Purpose This paper examines the relationship between family functioning (e.g. communication, closeness, problem solving, behavioral control) and adolescent weight status and relevant eating and physical activity behaviors. Methods Data are from EAT 2010 (Eating and Activity in Teens), a population-based study that assessed eating and activity among socioeconomically and racially/ethnically diverse youth (n = 2,793). Adolescents (46.8% boys, 53.2% girls) completed anthropometric assessments and surveys at sch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
182
1
20

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 177 publications
(224 citation statements)
references
References 33 publications
21
182
1
20
Order By: Relevance
“…Berge et al studied daily breakfast consumption and family functioning by measuring family communication, closeness, problem solving and behavioural control (20) . Franko et al studied breakfast frequency and family cohesion measured by emotional bonding, supportiveness, family boundaries and spending time together (24) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Berge et al studied daily breakfast consumption and family functioning by measuring family communication, closeness, problem solving and behavioural control (20) . Franko et al studied breakfast frequency and family cohesion measured by emotional bonding, supportiveness, family boundaries and spending time together (24) .…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be hypothesized that a shared meal may lead to better family functioning. Others have found an association between family functioning and shared family meals (20) and the family meal has been used as a measure of family functioning (61) . The applied family functioning measures are widely used and the internal reliability has been tested in the present study sample.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, family communication, specifically the expression of emotion, is associated with thoughts of disordered eating (Arroyo & Segrin, 2013;Segrin & Flora, 2011). Berge, Wall, Larson, Loth, and Nuemark-Sztainer (2013) found that family functioning was related to adolescents' health behaviors, such as eating fruits and vegetables, physical activity level, and weight. Moreover, family communication patterns directly affect health attitudes (Baiocchi-Wagner & Talley, 2013) and body dissatisfaction (Taniguchi & Aune, 2013).…”
Section: Family Communication Patterns Theorymentioning
confidence: 99%
“…Family communication is related to health outcomes in children and adolescents (Arroyo & Segrin, 2013;Baiocchi-Wagner & Talley, 2013;Berge et al, 2013), but there is no research in terms of how family communication affects children's perceptions of others' health.…”
Section: The Current Studymentioning
confidence: 99%